Grade Inflation in Higher Education: A Guidance for Future Research and Solutions - Mustapha, Ramlan; Mat Som, Zulkifli Mat Zulkifli; Jafar, Mohd Fairuz; Sulaiman, Suriati; Sarkowi, Azizah; Sarkowi, Azizah; Shidki, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The groundbreaking phenomenon of grade inflation has been discussed widely as student grades have increased significantly regardless of their actual ability in many higher education institutions around the world. Such issue has alerted many parties due to the fact that the grade achievement gap has affected the credibility of the institutions involved. The increasing trend of grade inflation in many institutions of higher education has become the focal point for the researchers to take this issue seriously as it has significant negative implication on Malaysia higher education institutions particularly in Teacher Education Institutes. Although the issue of increasing grade inflation is considered important and received serious attention from various parties, to date no evidence-based study has been conducted to investigate the phenomenon in Malaysian higher education institutions. As such, this study has been proposed to examine the trend, causal factors and proposed solutions to overcome the issue of grade inflation at teacher education institutes in Malaysia based on critical analysis of various studies from the literature reviews.